AN ANALYSIS OF POLITENESS STRATEGIES USED BY EFL STUDENTS IN ORAL PRESENTATION AT UNIROW TUBAN - Christina I.T. Panggabean; Ulfa Yuliasari; Dindha Febryanti; Dholiful Hadi (Tarbiyatuna Kajian Pendidikan Islam, 2022)
Politeness is a need in education, a strategy to build character, and as a motivation in the class. The research is conducted to analyze politeness strategy. The research design of the study was descriptive qualitative and the subject was the EFL students of the sixth semester who took Research on ELT subject. There were 26 respondents whose politeness strategies were identified during classroom presentation. The research instruments of this study were observation checklist, video recorder, and field note. The writer collected the data by observation and documentation through the video presentation. The data were analyzed qualitatively using Brown and Levinson theory of Politeness Strategy. The result of the study showed that the students use all of politeness strategies but they do not used all sub strategies during presentation, which was bald on record, positive politeness strategy, negative politeness strategy, and off record and non-verbal strategy. The way they used politeness strategies by direct and indirect speech during delivery and question-answer section. There were 88 utterances consisting of different types of politeness strategies. The types of politeness strategies used by the students consisted of positive politeness strategy which occurred 32 times (36.4%), bald on record occur 26 times (29.5%), negative politeness strategy occurs 8 times (9.1%), Off record strategy occurs 6 times (6.8%) and the last is non-verbal strategy occurs 16 times utterances (18.2%). Positive politeness strategy gets the highest position in the data because speakers and hearers are in the same level of power and the interactions mostly occurred among the students.